إضاءات على بعض جوانب عملية الإصلاح الاقتصادي في سورية " التحديات وإمكانية الاستفادة من تجارب الدول الأخرى" (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يحتل موضوع الإصلاح الاقتصادي موقع الصدارة في الجدل والنقاش الدائرة على الصعيدين الاقتصادي والسياسي في بلدنا وعليه فان هذا البحث يهدف إلى مناقشة بعض جوانب عملية الإصلاح الاقتصادي في سورية, وذلك من خلال استعراض المبررات والتحديات التي تستوجب عملية الإصلاح, وكذلك استعراض المراحل التي مرت بها عملية الإصلاح في سورية, وأيضاً استعراض بعض التجارب العالمية في موضوع الإصلاح الاقتصادي وإمكانية الاستفادة منها ليتلخص هذا البحث في النهاية إلى وضع نتائج وتصورات في إطار برنامج مقترح يتضمن بعض ملامح الإصلاح الاقتصادي المطلوب. The subject of economic reform has been recently placed at the top of hot discussions and debates at both economic and political levels in Syria. This research is devoted to the discussion of some aspects of the Syrian Economic Reform (SER). It outlines SER' justifications and challenges, which created an essential need for such process. It also presents concurrent steps of the SBR. In addition, the study descries some International developments on the subject of economic reforms, and in particular the extent to which Syrian can benefit from those situations. Finally, the research will result in some conclusions and suggestions in the form of recommended program with reference to the required features of the SER.